Data on zinc chelates of glycine as a growth and survival enhancer in hybrid grouper and whiteleg shrimpMendeley Data - Sarmila Muthukrishnan; Donny Kai Hee Tey; Wen Chen Wee (Data in Brief)
The dataset demonstrates the efficacy of Aqua Ectogon-284, a zinc chelates of glycine, as a dietary supplement to enhance growth and survival in hybrid grouper (Epinephelus fuscoguttatus ♀ × E. lanceolatus ♂) and whiteleg shrimp (Penaeus vannamei). Two concentrations (1g/kg feed and 2g/kg feed) were evaluated against a control group to identify an optimal dosage that maximizes growth and health outcomes. Both the species exhibited improved growth performance and survival rates with dietary supplementation. The hybrid grouper fed a 1g/kg diet achieved the highest final weight of 100.00 g, with significant increases in length and survival rates of 96.00%. Similarly, whiteleg shrimp demonstrated enhanced final weights and survival (94.67%) with the same treatment. These findings revealed that zinc chelate glycine increased the growth rate and reduced mortality in farmed species.